2020
DOI: 10.1017/s0305000920000458
|View full text |Cite
|
Sign up to set email alerts
|

Parent education to improve early language development: A preliminary evaluation of LENA StartTM

Abstract: Parents play an important role in creating home language environments that promote language development. A nonequivalent group design was used to evaluate the effectiveness of a community-based implementation of LENA Start™, a parent-training program aimed at increasing the quantity of adult words (AWC) and conversational turns (CT). Parent-child dyads participated in LENA Start™ (n = 39) or a generic parent education program (n = 17). Overall, attendance and engagement in the LENA StartTM program were high: 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(50 reference statements)
0
3
0
1
Order By: Relevance
“…The primary objective of the LENA system is to provide users (e.g., parents, educators, researchers) with a tool for describing children's natural language environments without requiring any technical expertise nor access to computing resources. The LENA Foundation offers a variety of programs catered to the specific needs of its consumers, such as educational programming for parents (LENA Start) and educators (LENA Grow) that instruct users on how to use the recording device and software to track their own language usage around children (Elmquist et al, 2021). The LENA Foundation also offers a cloud-based processing system (LENA SP) for researchers who wish to collect and process data from multiple sites.…”
Section: Two Systems For Long-form Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objective of the LENA system is to provide users (e.g., parents, educators, researchers) with a tool for describing children's natural language environments without requiring any technical expertise nor access to computing resources. The LENA Foundation offers a variety of programs catered to the specific needs of its consumers, such as educational programming for parents (LENA Start) and educators (LENA Grow) that instruct users on how to use the recording device and software to track their own language usage around children (Elmquist et al, 2021). The LENA Foundation also offers a cloud-based processing system (LENA SP) for researchers who wish to collect and process data from multiple sites.…”
Section: Two Systems For Long-form Recordingsmentioning
confidence: 99%
“…LENA is a flexible system, with use cases in basic research (Weisleder and Fernald, 2013;Romeo et al, 2018), early diagnosis of developmental disorders or delay (Richards et al, 2010), and early childhood intervention (Wong et al, 2018;Ferjan Ramírez et al, 2019;Elmquist et al, 2021).…”
Section: Uses Of the Lena System And Available Datamentioning
confidence: 99%
“…The importance of the physical and social/communicative context to language development is shown in the success of intervention studies that manipulate the context. It has been found that directing the parent to increase utterance input, respond to the child's lead, and create opportunities for language learning (interactive book reading, direct teaching of vocabulary and narrative skills) can improve language learning outcomes (Beecher & Van Pay, 2020;Burgoyne et al, 2018;Elmquist et al, 2020;Fricke et al, 2017).…”
Section: Language and Conceptual Acquisition Are Necessarily Situated...mentioning
confidence: 99%
“…Both systems include online project management and database-reporting systems in support of monitoring project progress and usability and scaling up individual users. Beecher and Van Pay ( 2020 ) reported a successful application of LENA Start delivered to parents in a library context, and Elmquist et al ( 2020 ) reported preliminary findings from a community-based parenting program.…”
Section: Interventions At the Child/family Levelmentioning
confidence: 99%